(3GdCTHGg hGdfXGFQ aj aQhY GdMfjaIs - (3GdeUQj GdMfaj, GHf fLje, Rjf GdOjf Hf EHQGgje Hf eMeO, (B970 (3g`s ((3eUWai Hf SYOi gOGdgs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi eG CfYe hUdi Gddg Ydi SjOfG eMeO hHYO aEf Gdabg CTQa GdYdhe bOQG CdaJ cJGHG eNJUQG aj GdVhGHW SejJg HGdahGFO GdRjfjI aj abg GdMfajI aCdgeJ Cf CUfY cJGHG Ydi GdfeW GdSGHb HYO CSejJg GdCTHGg hGdfXGFQs
(3BNQgG (B:s
(3hPcQJ GdebQQ JTgjQG aZVH hbGd bWYc Gddg ceG bWYJ cJHj aGHJdj HGdCJQGc MJi LYdhg Ydi QCS TLQJjf aJbWY fUajfs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B969 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 64s
(3eYLe GdeDdajf (B1 / 740s
(3cTa GdXfhf (B1 / 98s
(3TPQGJ GdPgH (B8 / 358s
Keywords: (3Gdabg GdMfHdjs